Implementasi program sertifikasi halal untuk meningkatkan potensi perekonomian UMKM Desa Klampisrejo Kecamatan Kraton Kabupaten Pasuruan - Almaniq, Dian Hafida Fitranti; Riyanto, Muhamad (Islamic Economics Study Program, Faculty of Sharia and Islamic Economics, Universitas Annuqayah, 2024)
In the global halal product market globalization, halal certification has become crucial for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. However, many MSMEs need help meeting these certification requirements, affecting their access to an increasingly expanding market. This research aims to explore the impact of halal certification implementation on MSMEs in Klampisrejo Village, Pasuruan Regency, Indonesia, focusing on consumer trust, market access, and product quality. A qualitative approach uses in-depth interviews and participatory observation as primary data collection techniques. The analysis shows that the implementation of halal certification for MSMEs (Micro, Small, and Medium Enterprises) products in Desa Klampisrejo has been successfully carried out for the presence of halal certification provides a sense of security and peace of mind for Muslim consumers when purchasing and consuming products with the halal label. The results of this research have important implications for developing policies and more effective support strategies for MSMEs in navigating the global halal product market competition.